Studi tentang Kesiapan Pengadilan Agama Ambon Kelas IA terhadap Penyelesaian Sengketa Perbankan Syariah Menurut Undang-Undang Nomor 3 Tahun 2006 Tentang Pengadilan Agama Pasca Penetapan Undang-Undang Nomor 21 Tahun 2008 Tentang Perbankan Syariah - Hasan, Hasan; Shardi, Akbar M (TAHKIM, 2017)
This research titled Study About Preparation of Ambon's Religion Justice class IA to solve Syariah bank dispute Based On UU No. 3, 2006 After UU's Establishments No. 21 On 2008 About Syariah Bank. In its development researcher lifts about problem subject how Preparation of Ambon's Religion Justice class IA to solve Syariah bank dispute Based On UU No. 3, 2006 After Establishments UU No. 21 On 2008 About Syariah Bank. Observational method that used in this study; field reasearch's observational type by orients on descriptive kualitatives, normatives approaching, data collecting method using interview method whereas analisis data used are deduction, induction and comparability. There is result research, esentially, Justices of Ambon's religion Class IA, was ready in order to solve syariah bank dispute evident judge have preparing self variously; often gets discussion with judge humanity, study orders concerning with syariah economic for example; Islamic Law compilation, Jurisdictional compilation of Syariah Economic, UU No. 21 on 2008 About Syariah Bank and fiqhi's books includes classic book and also fikhi kontemporer's book at single-sided. On the other side religion justice judge class IA Ambon tries to follow executed program by Supreme Court concerning education and syariah's economy training but haven't available graduate one. Meanwhile dispute working out performing syariah's bank was carried on Ambon's religion justice Class IA Caused by; human resource of judge preparation situation is still less be equal, occasionally, judge mutation happened in religion justice, troublesome society unwillingness at religion justice because need much cost and time, and its reducing socialization various rule that manage syariah economic or syariah's banking to Ambon's city society.